Causes of First Year Student Dropout, Private University of Chile: Cohorte 2020. Universidad Privada de Chile - Varela Gangas, Patricia; Imbarack Mufdi, Patricia; Sierra Tucas, Marjorie (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
University desertion will be understood as “The abandonment of a study program before obtaining the corresponding title or degree, considering a time long enough to rule out the possibility of reincorporation” (Himmel, 2002, p. 94). In Chile it is a problem of the national reality and that, in general, affects the different Institutions of Higher Education. The objectives set for the research lie in knowing and analyzing the causes of the dropout of the 2020 cohort students, from the undergraduate careers of a private University of Antofagasta, Chile. The conclusions will be aimed at responding from the research objectives, as well as being able to break down each of the variables, identifying and describing each of these factors.